Peningkatan Karier Karyawan : Analisis Program Pengembangan Karier dan Motvasi Kerja Menggunakan Metode Crossbars di PT Wasteforchange Alam Indonesia - Fara Nia Williana; Zahra Zahra; Athiy Dina Rosihana (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of career development and work motivation on employee career improvement at PT Wasteforchange Alam Indonesia. The method used is a descriptive quantitative approach with a population as well as a sample of 45 permanent employees. Data collection was carried out through Likert scale questionnaires, semi-structured interviews, documentation, and literature studies. Data analysis techniques include descriptive percentages and cross-tabulation to identify the tendency of influence between variables. The results of the study show that career development is in the high category and makes a positive contribution to employee career improvement. Similarly, work motivation is in the high category and has a significant influence in supporting career acceleration. Cross-tabulation analysis revealed that the combination of career development and work motivation contributed more strongly to career advancement than the partial influence of each variable. These findings confirm the importance of a human resource management strategy that balances aspects of career development and work motivation in creating more optimal career opportunities. The practical implication of this research is the need for companies to design career development programs that are integrated with an adaptive work motivation system, in order to increase employee retention and productivity in a sustainable manner. This research also provides a foundation for HR policy making based on a holistic and participatory approach.